Relationship between DNA degradation ratios and the number of loci detectable by STR kits in extremely old seminal stain samples. Issue 5 (September 2015) - Hara, M.; Nakanishi, H.; Takahashi, S.; Nagai, A.; Yamamoto, T.; Yoneyama, K.; Saito, K.; Takada, A.
Highlights DNA degradation ratio correlated moderately with storage duration. The detected loci in STR kits correlate with DNA degradation ratio. The number of detectable STR loci could be estimated by quantifying two amplicons.